Correlation between ABO Blood Groups and Blood Sugar Levels as Cross Sectional Study of Healthy Student, In Wasit University - Abbood , Dhoha Hamzah; Hussein, Asyad Abdul-Abbas; Al Salman , Asawer Abdul Jabbar; Salih, Alyaa Abdulhadi; Jaleel, Isra’a; Mjefi, Manahel Hadi; Hamzah, Nuha Alaa; Alabas, Rusul Laith Abd (American Journal of Biodiversity, 2024)
Objective: Our study have been performed in wasit, Iraq to look at association of blood groups and blood sugar level. Samples and methodology: It was a cross sectional study conducted at University of wasit . The blood samples were collected from student in year 2024 involving 75 samples were taken from both male and female, healthy individual with age ranging from (18-25) years, the samples were tested for ABO blood groups using (ABO_kit ) additionally, the samples were submitted to Glucometer machine to evaluate the glucose level. Result: Chi-square test result showed all blood groups especially B have positive association with blood sugar level which involve 2.82 mg / dl and p=0.0469 also statistical analysis appeared the blood groups O is the most dominant No 26 (34.670 %) followed by other blood groups , the statistical data explained a highly significant difference in the distribution of blood types , (p<0.01).Our research showed there was no significant difference (NS) achieved between individuals with blood sugar level Over than 100(mg/dl)that are prediabetes (developing diabetes in the future) and individual with blood sugar level less than 100 (mg /dl( Conclusion: The research suggests a positive association between ABO blood groups and blood glucose levels. It was found that blood group O is the most prevalent, while group AB is the rarest, with a frequency of 10 (13.33%). Further large-scale studies in different ethnic populations are needed to confirm these findings.